Blogs vs vlogs: evaluation of chinese audience resonance in slow tourism - Wang, Meng; Abd Rahman, Azmawani; Abdul Aziz, Yuhanis; Adzharuddin, Nor Azura (Akdeniz University Publishing House, 2024)
Slow tourism has been implemented in rural areas and small towns in China for over a decade. However, the effectiveness of utilizing blogs or vlogs for promoting slow tourism destinations varies significantly. This study explored the reasons for the differences in marketing effectiveness of slow tourism destinations from the perspective of audience resonance. A total of 231 college students participated in the study and PLS-SEM was employed for hypothesis testing. The study results revealed positive impacts of value accord, expectation fitting, and cultural credibility on cognitive resonance. Additionally, there were positive impacts of slowness, self-congruence, and entertainment on emotional resonance. These factors further contribute to audience resonance in slow tourism. Emotional resonance turned out to be the driving factor of audience resonance. In addition, this research has also proved that the degree of resonance is the same whether the information carrier is text, photo, or video. No prior research has quantitatively validated the audience resonance in a slow tourism setting. This study addresses this knowledge gap and adds to the body of knowledge on slow tourism marketing and resonance theory.